2020
DOI: 10.1177/1473325020932374
|View full text |Cite
|
Sign up to set email alerts
|

“We belong to nature”: Communicating mental health in an indigenous context

Abstract: The approach to standardized services in Norwegian mental health care is tailored to the needs of the majority population, focusing on diagnoses and overshadows an approach that understands, values and emphasizes Sámi storytelling and everyday life. This study aims to contribute knowledge regarding the promotion of user involvement in mental health care from the perspectives of Sámi mental health care users. A narrative approach offers an opportunity to unravel an indigenous approach to mental health care and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Previous research confirms that living in close relations with the land and nature can be significant for the Sami people [32,33]. Sørly et al [33] for instance, concluded that living in close relation with nature was of significance in the healing process for Sami patients with mental health challenges.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Previous research confirms that living in close relations with the land and nature can be significant for the Sami people [32,33]. Sørly et al [33] for instance, concluded that living in close relation with nature was of significance in the healing process for Sami patients with mental health challenges.…”
Section: Discussionmentioning
confidence: 74%
“…Previous research confirms that living in close relations with the land and nature can be significant for the Sami people [32,33]. Sørly et al [33] for instance, concluded that living in close relation with nature was of significance in the healing process for Sami patients with mental health challenges. Our participants confirmed this finding, even if in our study the feelings of well-being in connection to nature did not necessarily require having physical access to nature, as leaning on memories from past experiences in nature could also enhance feelings of well-being among our participants.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…In the report, it is stated that: "Cultural heritage helps to create belonging and understanding of our places in the times. This is expressed by cultural heritage saying something about how we are and what we have been, where we are and where we are going" [32] (p. 22) If you study aboriginal cultures, different tribes, or old languages you can find a trace of sustainability a long way back [52][53][54]. In the Nordic countries live the Sámi people, who are an arctic indigenous population group living in Norway, Sweden, Finland, and Russia.…”
Section: Traditional Knowledge and Sustainabilitymentioning
confidence: 99%
“…The knowledge consists of cultural, heritage, traditions, and ways of living [26]. Today, the dominant view of ecological, social and health models consists of a Westernized approach, but the fact is that aboriginal population groups, such as Mãori or Sámi culture, embrace a holistic approach to ecosystems, where the care for place and landscape is of high relevance as it features a sense of belonging [53,54].…”
Section: Traditional Knowledge and Sustainabilitymentioning
confidence: 99%